Measurement of changes in torsional stiffness of press‐formed paperboard packages induced by heat load utilizing a developed measuring device. Issue 10 (5th July 2021) - Tanninen, Panu; Leminen, Ville; Matthews, Sami; Niini, Arvo; Varis, Juha
Abstract: The press‐forming process and the effects of parameter variation on the forming process have attracted great interest lately. The dimensional accuracy of the formed trays and the rigidity and stability of the packages are crucial factors for functionality in packaging lines, especially in fast operating machinery. The torsional stiffness of trays must be at a sufficient level to ensure the functionality in subsequent processes and logistics. The objective of this study was to develop and build a device for measuring the torsional stiffness of whole tray packages, to verify its functionality and to investigate the effect of heat load transferred to paperboard material on the torsional stiffness of the formed trays. The operation of the novel torsional stiffness tester was confirmed, and the tester was found to be suitable for measuring the thermal response of the sample materials and the effect of the fibre direction. Thus, the analysed material does not need to have a homogeneous stiffness property since the differences are noticeable in the measurement results. In addition, the results indicate that tray blanks should be die cut in the machine direction of the paperboard. The torsional stiffness of the tray packages increases, and the outer dimensions decrease as a function of the heat input. The first feature is desirable for packaging functionality and the second feature can be compensated by competent packaging design. To conclude, the use of higher mould temperatures is recommendable if the integrity of the package material is not compromised. Abstract : The torsional stiffness of press‐formed paperboard trays must be at a sufficient level to ensure the functionality in packaging lines, especially in fast operating machinery and logistics. The objective of this study was to develop and build a device for measuring the torsional stiffness of whole tray packages. The operation of the novel tester was confirmed, and the tester was found to be suitable for measuring the thermal response of the sample materials and the effect of the fibre direction.